Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s10811-007-9308-y
|View full text |Cite
|
Sign up to set email alerts
|

Production, use and fate of Chilean brown seaweeds: re-sources for a sustainable fishery

Abstract: Chile is an important producer of brown seaweeds representing 10% of world supply. Landings of Chilean kelp fluctuated between 40,000 t.year −1 in the early '80s to 250,000 t.year −1 more recently. Commercialized algae come from natural populations and no mass-cultures of involved species have been established. Four species of brown algae are commercially collected in the country: Lessonia trabeculata, L. nigrescens, Macrocystis pyrifera and M. integrifolia. Since 2000, the demand of alginate sources and food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
73
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 33 publications
1
73
0
5
Order By: Relevance
“…In temperate habitats, kelp species are harvested through whole-plant or vegetative tissue removal (Tegner & Dayton 2000, Steneck et al 2002, 2013, Vásquez 2008. Along the Chilean coast, the dominant kelp species inhabiting intertidal habitats are Lessonia spp., which are heavily harvested by local fishermen who traditionally remove the whole plant from the substrate (see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In temperate habitats, kelp species are harvested through whole-plant or vegetative tissue removal (Tegner & Dayton 2000, Steneck et al 2002, 2013, Vásquez 2008. Along the Chilean coast, the dominant kelp species inhabiting intertidal habitats are Lessonia spp., which are heavily harvested by local fishermen who traditionally remove the whole plant from the substrate (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…(formerly L. nigrescens) were recently separated into 2 species: L. spicata, which is found between 42° and 30° S, and L. berteroana, which is distributed between 17° and 30° S and forms singlespecies stands (Tellier et al 2011, González et al 2012. Kelp fishery in Chile lands up to 300 000 dry tons annually and has an economic value exceeding US$70 million (Vásquez 2008). Harvesting of this ecologically relevant species is managed following a spatial rule that is based only on the spatial structure of mature kelp stands, but this spatial management approach does not consider the mechanisms underpinning the development of this spatial heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The two algae were selected since L. nigrescens and, especially, D. antarctica are healthy and nutritious edible seaweeds for humans and animals (Ortiz et al 2006) and are also used as a natural alginate source (Skjermo et al 2006;Vásquez 2008). It is reported that L. nigrescens has high sorption capacity of arsenic from the surrounding aquatic media, as is shown in samples collected in the Valparaiso Bay, Chile ).…”
Section: Introductionmentioning
confidence: 99%